2012
DOI: 10.1007/s13762-012-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of biodegradation of diesel fuel by enriched microbial consortia from polluted soils

Abstract: Three microbial consortia were isolated from three polluted soils located at an oil refinery and acclimated to grow on diesel fuel as the sole carbon source. Batch experiments were then conducted with the three consortia to study the kinetics of diesel biodegradation. The effects of temperature (25, 30 and 35°C) and diesel concentration (0.5, 1 and 3 %) on the biodegradation of diesel were analysed. Several species were identified in the acclimated microbial consortia, and some of them appeared in more than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…This consortium of microorganisms was maintained and enriched with Bushnell-Hass Broth (BHB) as the mineral medium (the composition of the medium per litre of deionised water was 0.20 g l −1 MgSO 4 , 0.02 g l −1 CaCl 2 , 1.00 g l −1 KH 2 PO 4 , 1.00 g l −1 (NH 4 ) 2 HPO 4 , 0.05 g l −1 FeCl 3 and 1.00 g l −1 KNO 3 ) and diesel hydrocarbon as the sole carbon source (1.0% v/v). After the enrichment process, some of the microorganisms in the consortium were identified, including Staphylococcus lentus, Stenotrophomonas maltophilia and Pseudomonas fluorescens, as reported in a previous work (Moliterni et al, 2012). According to previous studies, these species are commonly found in hydrocarbon-polluted soils.…”
Section: Micro-organismsmentioning
confidence: 82%
See 2 more Smart Citations
“…This consortium of microorganisms was maintained and enriched with Bushnell-Hass Broth (BHB) as the mineral medium (the composition of the medium per litre of deionised water was 0.20 g l −1 MgSO 4 , 0.02 g l −1 CaCl 2 , 1.00 g l −1 KH 2 PO 4 , 1.00 g l −1 (NH 4 ) 2 HPO 4 , 0.05 g l −1 FeCl 3 and 1.00 g l −1 KNO 3 ) and diesel hydrocarbon as the sole carbon source (1.0% v/v). After the enrichment process, some of the microorganisms in the consortium were identified, including Staphylococcus lentus, Stenotrophomonas maltophilia and Pseudomonas fluorescens, as reported in a previous work (Moliterni et al, 2012). According to previous studies, these species are commonly found in hydrocarbon-polluted soils.…”
Section: Micro-organismsmentioning
confidence: 82%
“…However, the average diesel removal efficiency was only approximately 12%. In previous studies on diesel biodegradation using the same microbial consortium (Moliterni et al, 2012) and using the biobarrier (Mena et al, 2015), it was found that the biodegradable fraction of the diesel was approximately 70% (expressed as COD). Thus, only a small portion of the biodegradable fraction of the diesel hydrocarbons was removed through the Bio treatment in two weeks, which could be due to the slowness of the static in situ biological process.…”
Section: Microbial Growth and Hydrocarbon Removal Under Different Sitmentioning
confidence: 98%
See 1 more Smart Citation
“…Continuous‐flow systems may need less time to consume the substrates of interest but batch studies may treat higher substrate concentrations without many of the problems associated with continuous‐flow designs. For example, our reactor system reached >95% degradation in only 1.5 h, whereas an aerobic consortia batch study needed 40 h to degrade >80% at an initial diesel concentration 3‐fold higher than ours . In this particular case, we used lower diesel concentrations since Monod kinetics can be applied only for low to intermediate pollutant concentrations.…”
Section: Resultsmentioning
confidence: 88%
“…For example, our reactor system reached >95% degradation in only 1.5 h, whereas an aerobic consortia batch study needed 40 h to degrade >80% at an initial diesel concentration 3-fold higher than ours. 34 In this particular case, we used lower diesel concentrations since Monod kinetics can be applied only for low to intermediate pollutant concentrations. In addition, a batch diesel degradation study at 30 ∘ C by a pure culture of the biosurfactant producing Gordonia alkanivorans diesel consumption and monitored cell dry weight at designated time intervals.…”
Section: Monod Parametersmentioning
confidence: 99%